Is the wear coefficient dependent upon slip amplitude in fretting?: Vingsbo and Söderberg revisited - Pearson, S.R.; Shipway, P.H. (Elsevier, 2014)
More than 25 years ago, Vingsbo and Söderberg published a seminal paper regarding the mapping of behaviour in fretting contacts (O. Vingsbo, S. Söderberg, On fretting maps, Wear, 126 (1988) 131–147). In this paper, it was proposed that in the gross-slip fretting regime, the wear coefficient increased by between one and two orders of magnitude as the fretting displacement amplitude increased from around 20 µm to 300 µm (defined as the limits of the gross-slip regime).